Penerapan Arsitektur Vernakular pada Redesain Terminal Bus Tipe B Kota Tanjung Balai - Tambunan, Raja Yusuf Novaldi Tambunan; Saraswaty, Rina (Universitas Medan Area, 2025)
Tanjung Balai bus terminal has experienced a decline in function due to inadequate facilities, causing many bus companies to cease operations there. This situation, combined with the presence of illegal terminals that create congestion and lack comfort, has driven the redesign of the terminal into a Type B terminal that meets standards. The research employs a qualitative descriptive method, including site analysis, literature review, and field surveys to identify negative environmental impacts. The redesign aims to restore the terminal's function by applying neo-vernacular Malay architecture, creating comfortable facilities, and supporting infrastructure development. This project is expected to improve transportation quality, enhance public spaces, and provide benefits to the surrounding community.